2017
DOI: 10.3892/etm.2017.4898
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 antagonist suppresses airway remodeling in asthma by inhibiting the T-helper 2 response

Abstract: Airway remodeling is a hallmark of bronchial asthma. Our group has previously reported that the thymic stromal lymphopoietin (TSLP), an airway epithelial-derived cytokine, has a central role in the pathogenesis of airway remodeling, and that toll-like receptor (TLR) 4 signaling in epithelial cells may trigger T-helper 2 (Th2) immune responses by overexpression of TSLP. However, it is currently unclear whether TLR4 is a target in the treatment of airway remodeling in asthma. The present study established a hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In contrast, the increase in neutrophils was only 3-fold in the 4 HDM models compared to Saline controls. Our observations in the 4- and 8-week HDM groups are consistent with previously reported 5-week models 19 , 20 , 25 , where robust increases in eosinophils were also accompanied by significant increases in the BAL neutrophil cell counts, with the overall absolute neutrophil counts ~10-fold higher than the absolute eosinophils.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the increase in neutrophils was only 3-fold in the 4 HDM models compared to Saline controls. Our observations in the 4- and 8-week HDM groups are consistent with previously reported 5-week models 19 , 20 , 25 , where robust increases in eosinophils were also accompanied by significant increases in the BAL neutrophil cell counts, with the overall absolute neutrophil counts ~10-fold higher than the absolute eosinophils.…”
Section: Discussionsupporting
confidence: 92%
“…Reversible airflow obstruction, airways inflammation, AHR to contractile agonists (spasmogens, such as methacholine or histamine) and airway remodeling are defining features of asthma 7 , 10 . Airways inflammation and enhanced MCh-responsiveness are observed in virtually all experimental models of allergic airways inflammation currently used 12 , 17 , 20 23 , 25 , 26 , with varying degrees depending on the dose, frequency, duration and type of allergen exposure 11 , 19 . Although goblet cell hyperplasia is observed as early as day 12 in our model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TLR4-signaling inhibition or HMGB1 neutralization reduces the pathologic features of asthma. For example, treatment of TAK242 in an HDM-induced asthma animal model suppresses airway remodeling in asthma by inhibiting the T-helper 2 response, 31 ameliorates combined allergic rhinitis and asthma syndrome (CARAS) by reducing inflammatory monocytes infiltration in mice model. 32 Moreover, HMGB1 neutralization attenuation of neutrophilic airway inflammation in asthma by suppressing Th17 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial activity of soya PC may be due to inhibition of TLR4 signaling‐mediated inflammatory responses and airway remodeling. It is well reported that activation of the MyD88‐dependent intracellular signaling pathway of TLR4 leads to activation of NF‐κB and increases the gene expression of inflammatory cytokines which drive the activation of mucosal DC cascades and airway remodeling …”
Section: Discussionmentioning
confidence: 99%